Evaluating soil rhizobacteria for their ability to enhance plant growth and tuber yield in potato - Oswald, A (2010)
The authors thank the Papa Andina Initiative of the International Potato Center (CIP), the ALTAGRO project and Consejo Nacional de Sciencia, Tecnologia, e Innovacion Tecnologica (CONCYTEC), Peru, for its financial support.